Innovation of Digital Communication in Public Complaint Services: The Case of the JAKI Application in the Smart Government Era - Nurul Suhesti; Ika Devy Pramudiana; R Ayu Erni Jusnita; Nihayatus Sholichah (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
The shift toward smart government has accelerated the digitalization of public services, yet empirical evidence on how digital communication innovations function as instruments of participatory governance remains limited. This study aims to analyze digital communication innovation through the JAKI (Jakarta Kini) application in public complaint services within the smart government framework of DKI Jakarta Province. Guided by a qualitative single instrumental case study design, data were gathered from 19 informants via in-depth interviews, structured non-participant observations, and document analysis. Informants included five CRM officers from Diskominfotik, six OPD staff members from three key agencies, and eight active JAKI users selected through purposive and snowball sampling. Data were analyzed using thematic content analysis and interpreted through the Van Meter and Van Horn policy implementation model. The findings reveal that JAKI has successfully shifted public complaint management from a one-way reporting mechanism to a two-way interactive system, evidenced by a 77.4% increase in report submissions from 98,177 (2021) to 174,147 (2024), with resolution rates consistently above 96%. However, the communication pattern, while technically interactive, has not yet achieved substantive symmetry because citizen feedback rarely influences formal policy revisions. Key determinants of implementation effectiveness include inter-agency coordination through the CRM system, implementer commitment across OPDs, and citizens' digital literacy levels. This study concludes that JAKI represents a meaningful innovation in participatory governance. However, sustained effectiveness requires stronger OPD capacity, equitable digital access for vulnerable groups, and institutionalized feedback mechanisms that translate complaint data into evidence-based policy decisions.